Strength of Mass - Trivedi, Nripesh (International Journal of Scientific Research and Management (IJSRM), 2024)
Electricity is generated by magnet as described in [1]. It produces heat and light which are the properties of fire. Thus, electricity is fire. Since electricity is generated by magnet [1], electricity is magnetic. Since electricity is fire, thus fire is also magnetic. The energy of the mass is fire as described in [2].  Since fire is magnetic (as described above) and is the energy of the mass [2], the strength of the material or mass lies in magnetism. The strength of the material is magnetism (a short-range force as evident by the magnetic force between two magnets), thus strength of the material lies in more magnitude of material in less volume. This is because, the material is joined by a short-range force (magnetism) as described in above statement that energy of the mass is magnetism. From previous statement, it could be seen that strength of mass/material lies in density. It is density since higher density means higher magnetic force in the mass for joining mass together.